Awareness on indoor air quality among Malaysian: case study at KL Sentral, Malaysia - M. Aminuddin, Normadihah; Mohd. Din, Shamzani Affendy; Afgani @ Eusoff, Yendo (Universiti Sultan Zainal Abidin (UNiSZA), 2017)
Introduction When people think about air pollution, they usually think about smog, acid rain, chlorofluorocarbon (CFC's), and other forms of outdoor air pollution. However, air pollution can also exist inside homes and other buildings. Every year, the health of many people is affected by chemical substances present in the air within buildings. Pollution also needs to be considered inside our homes, offices, and schools. Some of these pollutants can be created by indoor activities such as smoking and cooking. According to Shamzani (2007), Malaysians spend about 80 to 90% of their time inside buildings, and so their exposure to harmful indoor. This paper provides a lot of information concerning the topic in order to understand the indoor air pollution specifically due to airborne particulates or pollutants can be serious. It is therefore important to consider both indoor and outdoor air pollution.